A survey of current YouTube video characteristics - Che, Xianhui; Ip, Barry; Lin, Ling (Institute of Electrical and Electronics Engineers, 2015)
Given the impact of YouTube on Internet services and social networks, a healthy quantity of research has been conducted over the past few years. The majority of studies on traffic capture and evaluation were carried out prior to Google's acquisition of YouTube in 2007. Since then, there have been some changes made to the user policy and service infrastructure, including limits placed on video duration, file size, and resolution. This article depicts the latest YouTube traffic profiles and delivers updated and valuable information for future researchers. To obtain a detailed understanding of YouTube video characteristics, a customized Web spider was employed to crawl over a million YouTube videos. The study demonstrates consistency with previous research for major video streams while revealing that new categories of features have emerged within the YouTube service provision. Compared with traditional video repositories, YouTube exhibits many unique characteristics that could introduce novel challenges and opportunities for optimizing the performance of short video-sharing services.